Continuous synthesis of 2-tert-butyl phenol oxidation in gas-liquid segmented flow and its kinetic investigation. (2nd February 2022) - Liu, Ping; Ge, Haowei; Lu, Yuheng; Wang, Yujun; Du, Le; Zhu, Jiqin
Graphical abstract: Highlights: Heterogeneous catalytic oxidation of 2- tert -butyl phenol was achieved. Gas-liquid segmented flow was introduced for process safety and intensification. The formed secondary flow enhanced mass transfer and inhibited particle deposition. The yield of 2- tert -butyl-1, 4-benzoquinone was approximately 70% within 29.02 min. Kinetics of 2- tert -butyl phenol oxidation was studied based on experimental data. Abstract: The process to produce tert -butylhydroquinone from 2- tert -butyl phenol (2-TBP) is of great importance in the application of phenolic derivatives. However, the oxidation of 2-TBP to 2- tert -butyl-1, 4-benzoquinone (2-TBQ) as the first step is usually performed in traditional batch reactors, suffering the disadvantages of mass transfer limitation and potential risk of explosion. Herein, a safer process to enhance the catalytic oxidation was developed by introducing gas–liquid segmented flow in a microchannel reactor. The 2-TBQ yield was approximately 70% within 29.02 min while the time was 8 h to obtained almost the same yield (65%) in batch systems. CFD simulation was conducted, confirming that secondary flow was formed in liquid slugs. The corresponding intensive convection ensured the continuous and stable operation without particle sedimentation. On the basis of the enhanced mass transfer, the kinetics of 2-TBP oxidation was also investigated. The obtained reaction orders of 2-TBP and oxygen were 2.0948 and 0.4073, respectively.